2007
DOI: 10.1063/1.2825422
|View full text |Cite
|
Sign up to set email alerts
|

Stable indium oxide thin-film transistors with fast threshold voltage recovery

Abstract: Stable thin-film transistors (TFTs) with semiconducting indium oxide channel and silicon dioxide gate dielectric were fabricated by reactive ion beam assisted evaporation and plasma-enhanced chemical vapor deposition. The field-effect mobility is 3.3cm2∕Vs, along with an on/off current ratio of 106, and subthreshold slope of 0.5V/decade. When subject to long-term gate bias stress, the TFTs show fast recovery of the threshold voltage (VT) when relaxed without annealing, suggesting that charge trapping at the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 16 publications
2
61
0
Order By: Relevance
“…Vygranenko et al [52] and Reidl et al [53] found no state creation instability in their indium oxide TFTs. The oxide TFTs can however be sensitive to oxidation problems and always to charge trapping in the gate insulator [53][54][55][56].…”
Section: Featurementioning
confidence: 98%
“…Vygranenko et al [52] and Reidl et al [53] found no state creation instability in their indium oxide TFTs. The oxide TFTs can however be sensitive to oxidation problems and always to charge trapping in the gate insulator [53][54][55][56].…”
Section: Featurementioning
confidence: 98%
“…Particularly, transparent TFTs based on transparent metal oxides such as ZnO [3][4][5], In 2 O 3 [6], In-Zn-O (IZO) [7,8], In-Ga-Zn-O (IGZO) [9], and Al-Zn-Sn-O (AZTO) [10] have much attracted due to their advantages over conventional semiconductors and their good transparency in the visible range, a low process temperature, good large-area uniformity, and relatively high carrier mobility [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the promise of oxide semiconductors as an enabling technology is only likely to be realised when a combination of simple processing and high performance can be achieved. Among the many metal oxide semiconductors known [10,[22][23][24][25][26] the II-VI group compound ZnO has attracted most interest because of its non-toxicity [17] and exceptionally high electron mobility. [13,27,28] In its crystalline form at room temperature, ZnO is characterised by a wide bandgap (~3.4 eV) and high optical transparency.…”
mentioning
confidence: 99%